THE RELATIONSHIP OF NURSING KNOWLEDGE REGARDING NOSOCOMIAL INFECTIONS ON PREVENTIVE BEHAVIORS OF NOSOCOMIAL INFECTIONS IN SALAK HOSPITAL OPERATING ROOM: HUBUNGAN PENGETAHUAN PERAWAT TENTANG INFEKSI NOSOKOMIAL TERHADAP PERILAKU PENCEGAHAN INFEKSI NOSOKOMIAL DI RUANG BEDAH RS SALAK KOTA BOGOR - Yufi Yufi Aliyupiudin (Wijaya Husada, 2019)
Nosocomial infection or also called hospital-acquired infection occurs in patients who are hospitalized for at least 72 hours and the patient does not show symptoms of infection when admitted to hospital. Riskes data shows the level of nosocomial infection in Indonesia reaches 6-16% with an average of 9.8%. In 2006 Indonsia had the percentage of nosocomial infections was obtained in Lampung Province reached 4.3%, Jambi 2.8%, DKI Jakarta 0.9%, West Java 2.2%, then Central Java 0.5%, and Yogyakarta 0.8 %. Knowing the relationship between nurses' knowledge about nosocomial infections on the prevention behavior of nosocomial infections in the Salak hospital operating room Bogor in 2018 This type of research uses quantitative analytic descriptive study with Cross Sectional research design. The sampling method uses total sampling with the population are nurses in the operating room and data were obtained by 30 respondents. The data collection is obtained through questionnaires. The results showed that from a total of 30 respondents 17 respondents (56.7%) stated that nurses were well-informed, 18 respondents (60.0%) stated that nurses behaved positively. The results of the behavior of prevention of nosocomial infection there were 16 respondents (53.3%) nurses had knowledge with positive behavior. The results of statistical tests obtained p value = 0,000 which means that p value <0.05. At the conclusion of the statistical test, there was a relationship between nurses' knowledge about nosocomial infections on the prevention behavior of nosocomial infections in the operating room Salak hospital of Bogor in 2018